Anti-Inflammatory Activity Assay of Ethanol Extract of Agelas cavernosa Sponge using Protein Denaturation Method - Walid, Muhammad; Nila Oktaviani; Julian, Rixzal Aziz; Rohmah, Salis Alyatur; Achada, Dina; Dika, Ika Vina; Mahfur, Mahfur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Inflammation is a tissue response to cell damage, and alternative medicine is needed to treat this like a sponge. Indonesia is a country that has a lot of biodiversity originating from the sea. Agelas cavernosa is a sponge of the Demospongiae class, this class is the largest class that includes 90% of all types of sponges. Agelas Cavernosa sponge is known to contain triterpenoids and has antibacterial activity. Data on research on the activity of Agelas cavernosa sponge as an anti-inflammatory as far as researchers know has not been carried out. The aim of this study was to determine the anti-inflammatory activity of the ethanol extract of the Agelas cavernosa sponge. The research method was carried out using the protein denaturation method. The Agelas cavernosa sponge extracted with etanol 96%. The assay of anti-inflammatory with protein denaturation using spectrophotometry at wavelengths 660 nm. The results showed that the inhibition ability of 20% protein denaturation of ethanol extract of Agelas cavernosa was obtained at a concentration of 150 ppm. The results of the study showed that the IC50 of the ethanol extract obtained was 455.96 pppm, significantly different from the positive control of sodium diclofenac, which was 36.51 ppm. Based on the data obtained from the research results, it shows that the ethanol extract of Agelas cavernosa sponge does not have the potential as an anti-inflammatory.